Box Girder Bridge Design; State of the Art - Heins, Conrad P. (Engineering Journal, 1978)
The information that will be presented herein will pertain to straight and curved steel composite box girder bridges of moderate span length (50-250 ft) that are utilized for highway interchanges. Although the general theories are applicable to larger structures, the design formulas that have been developed and will be given herein are only suitable for the conventional highway bridge.